Abuse Experiencing Among the Adolescents Students in Irbid Secondary Schools - Aldahadha, Basim (Italian Sociological Review, 2018)
This study aimed at investigating the level of abuse experience due to the effect of gender, achievement, grade, family income, high qualification of one parent or both, number of children, order of birth, and student residency variables upon means of abuse experience AE, among students of first and second secondary grades in Qasabah of Irbid. The sample of the study consisted of (1567) students: (684) males. They were selected randomly using clustering method. The results of the study showed that the level of AE came in the low level. Additionally, there were significant effects for gender, achievement, family income, and student residency on AE, in favor of males, low achievements, less than 200, more than 200 less than 500. According to the order of birth variable, the results came in favor of the first and in favor of at mid. Finally, results came in favor who live with relatives, while there is no significant effect for grade, qualification of parent, and number of children.